2020
DOI: 10.1002/chem.202003862
|View full text |Cite
|
Sign up to set email alerts
|

Insights into LiAlH4 Catalyzed Imine Hydrogenation

Abstract: Commercial LiAlH 4 can be used in catalytic quantities in the hydrogenation of iminest oa mines with H 2 .C ombined experimental and theoretical investigations give deeper insighti nt he mechanism and identifies the most likely catalytic cycle. Activity is lost when Li in LiAlH 4 is exchanged for Na or K. Exchanging Al for Bo rG aa lso led to dramatically reduced activities. This indicates ah eterobimetallic mechanism in which cooperation between Li and Al is crucial. Potential intermediates on the catalytic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 40 publications
1
31
1
1
Order By: Relevance
“…They are (mostly) biocompatible, environmentally benign and with their high abundance in the crustal layer and oceans of earth, a low price per mole is guaranteed. Activity in this area has been steadily rising since the turn of the millennium with pioneering contributions by Harder, Hill, Okuda, Cheng and Stock, with several catalytic hydrogenations published [7–27] …”
Section: Methodsmentioning
confidence: 99%
“…They are (mostly) biocompatible, environmentally benign and with their high abundance in the crustal layer and oceans of earth, a low price per mole is guaranteed. Activity in this area has been steadily rising since the turn of the millennium with pioneering contributions by Harder, Hill, Okuda, Cheng and Stock, with several catalytic hydrogenations published [7–27] …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the insertion of HBpin into the C=N bond proceeds more readily for the bimetallic compound I [3i] . Harder and co‐workers reinforced this hypothesis by a DFT study in their report on LiAlH 4 ‐catalysed imine hydrogenation, where they showed that the bridging Al‐H‐Li interactions are maintained throughout the catalytic cycle [7c,g] …”
Section: Emerging Alkali‐metal‐mediated Applicationsmentioning
confidence: 95%
“…Motivated by the high potential of cationic Al catalysts like AlEt 2 + in CO 2 to methane conversion, [31] we systematically investigated the application of cationic Al catalysts in imine hydrogenation. While it is known that neutral Al compounds like Al i Bu 3 catalyse this reaction under harsh conditions (>100 bar H 2 , 100 °C) [32] and LiAlH 4 is an effective catalyst under relatively mild conditions (1 bar, 80 °C), [33,34] we now report a series of highly Lewis acidic cationic β‐diketiminate (BDI) Al catalysts. Similar as in the recently reported imine hydrogenation with cationic Zr catalysts, [35] the advantage of cationic (BDI)Al + catalysts is the facile control over electronics and sterics by tuning the ligand through variation of substituents.…”
Section: Introductionmentioning
confidence: 97%